Governance for decarbonising and regenerating urban precincts - Bunning, Jessica M. (Curtin University, 2015)
The PhD by publication explores the way governance can be improved to facilitate decarbonising and regenerating urban precincts. The thesis’ findings imply that although no over-riding governance system prevails, certain governance models and tools are promising to be more applicable for particular circumstances than others. Moreover, the causal principles and lessons learnt are instrumental in guiding other communities in improving urban governance and addressing the serious environmental and social problems of today.